2011
DOI: 10.3353/omp.15.87
|View full text |Cite
|
Sign up to set email alerts
|

A case report of necrotizing sialometaplasia with immunohistological findings and a review of the literature

Abstract: Abstract:We report a case of necrotizing sialometaplasia arising as bilateral ulcers in the palate of a 20-year-old Japanese female patient. Based on histopathological and immunohistochemical findings, we discuss how to distinguish the condition from neoplastic lesions such as squamous cell carcinoma or mucoepidermoid carcinoma. Histopathologically, the ulcer bed of granulation tissue contained hyperplastic capillary vessels, inflammatory cell infiltrates, necrotizing and degenerating palatal glands, and squam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Calponin and p-63 were detected in all stages of the salivary gland, preventing needless surgical resection. Immunohistochemical staining showed that p-63 positivity of the residual myoepithelial cells and CK-7 positivity of the metaplastic epithelial islands and the salivary ducts can help distinguish necrotizing sialometaplasia from similar conditions such as squamous cell carcinoma and mucoepidermoid carcinoma 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Calponin and p-63 were detected in all stages of the salivary gland, preventing needless surgical resection. Immunohistochemical staining showed that p-63 positivity of the residual myoepithelial cells and CK-7 positivity of the metaplastic epithelial islands and the salivary ducts can help distinguish necrotizing sialometaplasia from similar conditions such as squamous cell carcinoma and mucoepidermoid carcinoma 8 .…”
Section: Discussionmentioning
confidence: 99%
“…This lesion was first described in 1973 by Abrams et al [1]. However, it may be confused with malignant lesions both histopathologically and clinically, in particular squamous cell carcinoma and mucoepidermoid carcinoma [2]. …”
Section: Introductionmentioning
confidence: 99%
“…These lesions are relatively rare and benign. However, may be confused with malignant lesions both histopathologically and clinically, particularly squamous cell carcinoma and mucoepidermoid carcinoma [3,4]. We report the clinical and histopathological features of a case of necrotizing sialometaplaia of the hard palate in a young adult man.…”
Section: Introductionmentioning
confidence: 99%